Analisis Teknikal Pergerakan Harga Saham Individual Dengan Menggunakan Indikator Ichimoku Kinko Hyo Dan Moving Average Convergence Divergence (Studi Pada Perusahaan Jasa Sub Sektor Advertising Printing Media) - Novitasari Novitasari; Muhammad Agus Salim; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2020)
Abstract Ichimoku Kinko Hyo and moving Average Convergence Divergence on the movement of individual stock prices in the print media advertising service company.The population of this study consisted of 19 companies of advertising print media sub sector listed on the Indonesia. Stock Exchange in the daily stock price value. The samples used were 5 samples that met the criteria in research starting in2017-2019. The analytical method used was the stationarity test, correlation test and wax charts using Ichimoku Kinko Hyo and Moving Average Convergence Divergence.The results of the study show that research using the ichimoku kiknko hyo indicator and Diverging Moving Average Conversion can be used to study the development of individual stock prices in advertising print media sub-service companies.Keywords : Ichimoku Kinko Hyo, Moving